Translating the Meaning of Polysemy Terms in the Holy Qur’an: Problems and Solutions - Tamim, Abdelhadi M. Omer (Journal of Posthumanism, 2025)
This study aims to investigate the translatability of the meaning of polysemous terms in the Holy Quran. The Descriptive Analytical Method is employed since it suits such type of studies. The translation of Abdullah Yousif Ali (1989) is chosen. Some problems of translating the meaning of these terms are presented and the strategies to solve such problems are employed in order to reach a close meaning(s) to polysemous terms of the Holy Quran. Findings of the study revealed that though there are real difficulties in conveying the actual meaning, these strategies can render a close meaningful translation to these polysemous terms.